2011
DOI: 10.1016/j.ijhydene.2011.03.111
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of hydrogen distribution around fatigue crack on type 304 stainless steel using secondary ion mass spectrometry

Abstract: Fatigue SIMS a b s t r a c t Secondary Ion Mass Spectrometry (SIMS) analyses were carried out on type 304 austenitic stainless steel. On annealed specimen exposed to hydrogen (10 MPa, 358 K), Element Depth Profiles SIMS mode was able to describe quantitatively the hydrogen profile content computed by the Fick's law. Based on SIMS analyses on the wake of a fatigue crack (propagation in hydrogen gas at 0.6 MPa and RT), it was possible to compute an apparent diffusivity and solubility in the crack tip region. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…However, the local apparent diffusivity can be significantly greater under the influence of a metal fatigue process. For example, it has been shown that the apparent hydrogen diffusivity under fatigue is some five orders of magnitude greater than the standard hydrogen diffusivity for type 304 austenitic stainless steel exposed to 10 MPa of hydrogen pressure [32]. It follows that the real hydrogen concentration ahead the crack tip can be even closer to unity than that suggested by Fig.…”
Section: Hydrogen Concentration Ahead a Moving Crack Tipmentioning
confidence: 86%
“…However, the local apparent diffusivity can be significantly greater under the influence of a metal fatigue process. For example, it has been shown that the apparent hydrogen diffusivity under fatigue is some five orders of magnitude greater than the standard hydrogen diffusivity for type 304 austenitic stainless steel exposed to 10 MPa of hydrogen pressure [32]. It follows that the real hydrogen concentration ahead the crack tip can be even closer to unity than that suggested by Fig.…”
Section: Hydrogen Concentration Ahead a Moving Crack Tipmentioning
confidence: 86%
“…The previous works on the hydrogen distribution by using SIMS were conducted in austenitic steels, 13,16) or martensitic steel which contains a considerable amount of boundary defects and dislocations. 17) In contrast, to our best knowledge, the use of SIMS to detect diffusible hydrogen in ferritic steels has a less number of reports 18) owing to the larger diffusion coefficient and lower solubility of hydrogen than those in austenitic steels and martensitic steels.…”
Section: 11)mentioning
confidence: 99%
“…Hydrogen atoms prefer to move to such a stress field to increase their stability, promoting crack propagation [43,44]. The ratio of the crack length to the grain-boundary length (the crack ratio) was determined on the basis of FE-SEM and EBSD data (Fig.…”
Section: Effect Of Cu Addition On Crack Initiation and Propagationmentioning
confidence: 99%